Liver X receptor agonist T0901317 alleviates sepsis-induced acute lung injury by enhancing macrophage autophagy - Wang, Ben; Wang, Ran; Wu, Xueling; Zhong, Yu; Huang, Chaowang; Xu, Zhi; Guo, Liang (Frontiers in Pharmacology, 2025)
BackgroundThis study was aimed at identifying the effects of liver X receptor alpha (LXRα) on sepsis-induced acute lung injury (ALI) and clarifying its novel regulatory mechanisms using bioinformatics and experimental methods.MethodsBioinformatics analysis of the differentially expressed genes and functional annotations were performed. Lipopolysaccharide (LPS) was administered intraperitoneally for sepsis-induced ALI in a mouse model; then, the LXR agonist T0901317 (T0) was administered to the mice along with RAW264.7 macrophages for LXRα activation. We then performed hematoxylin and eosin staining, estimated the total protein in the bronchoalveolar lavage fluid, and detected the expressions of TNFα and IL6 by reverse transcription polymerase chain reaction to evaluate the inflammatory injury in the lung tissues. Autophagy was detected via immunohistochemistry, transmission electron microscopy, and Western blotting. RNA sequencing was then used to analyze the autophagy-related genes regulated by LXRα, and the cells were transfected with S100A8-siRNA to determine whether LXRα regulated inflammatory damage by regulating the autophagy-related gene S100A8. The clinical correlation between LXRα and S100A8 was determined through analysis of human transcriptome data.ResultsThe bioinformatics analyses revealed that LXRα (NR1H3) was downregulated in sepsis-induced ALI models and that LXRα might regulate autophagy. The animal- and cell-based experiments further verified these findings. The LXR agonist T0 was found to alleviate lung damage and reduce the expressions of inflammatory factors in the lung tissues and cells. After inhibiting autophagy with 3-methyladenine, the protective effects of T0 on inflammatory damage were shown to be inhibited. Subsequently, RNA sequencing of the macrophages was performed, and four genes (ABCG1, FASN, S100A8, and SNORD118) were obtained by intersection of the upregulated and downregulated differential genes with the autophagy gene set. However, among these genes, only S100A8 that was increased in ALI and decreased markedly after T0 treatment exhibited a negative correlation with T0. Following S100A8 knockdown in the macrophages with S100A8-siRNA, the IL-6 expression was noted to decrease in cells treated with T0+LPS+S100A8-siRNA than those treated with LPS+T0. Analysis of the human transcriptome data revealed a significant negative correlation between LXRα and S100A8 (R = −0.98, p < 0.001).ConclusionThe findings of this study suggest that T0 attenuates sepsis-induced pulmonary injury by promoting macrophage autophagy via suppression of S100A8 expression.